2012
DOI: 10.2224/sbp.2012.40.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Achievement Goals and Physical Self-Perceptions of Adolescent Athletes

Abstract: The relationship between achievement goals and physical self-perceptions of adolescent athletes was examined in this study. Participants were 208 adolescent athletes with a mean age of 16.35 + 0.48 years. Independent samples t tests, Pearson correlations, and regression analysis were used to analyze the data. The results showed that female athletes' masteryavoidance scores were higher than male athletes'. Mastery-approach goals were related to sports competence and global physical self-concept. Performance-app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Most of the studies had reported the intercorrelations amongst the achievement goals ( k range 48–54) with the most number of samples ( k = 54) for the performance-approach and performance-avoidance goals. Antecedents fitting all of Elliot's antecedent categories were found within the 47 studies: competence-based 27 , 28 , 29 , 34 , 36 , 37 , 39 , 40 , 41 , 42 , 47 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 58 , 59 , 60 , 64 , 66 , 67 , 69 , 68 ( k range 39–46), environmental-based performance oriented 28 , 33 , 34 , 35 , 37 , 39 , 41 , 47 , 48 , 49 , 52 , 55 , 56 , 57 , 58 , 62 , 66 , 67 , 68 , 69 ( k range 24–28) and mastery oriented 28 , 33 , 34 , 35 , 39 , 47 , 48 , 49 , 52 , 55 , 56 , 57 , 58 , …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Most of the studies had reported the intercorrelations amongst the achievement goals ( k range 48–54) with the most number of samples ( k = 54) for the performance-approach and performance-avoidance goals. Antecedents fitting all of Elliot's antecedent categories were found within the 47 studies: competence-based 27 , 28 , 29 , 34 , 36 , 37 , 39 , 40 , 41 , 42 , 47 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 58 , 59 , 60 , 64 , 66 , 67 , 69 , 68 ( k range 39–46), environmental-based performance oriented 28 , 33 , 34 , 35 , 37 , 39 , 41 , 47 , 48 , 49 , 52 , 55 , 56 , 57 , 58 , 62 , 66 , 67 , 68 , 69 ( k range 24–28) and mastery oriented 28 , 33 , 34 , 35 , 39 , 47 , 48 , 49 , 52 , 55 , 56 , 57 , 58 , …”
Section: Resultsmentioning
confidence: 94%
“…A total of 47 published studies found in Table 1 were located that met the inclusion criteria. 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 69 , 70 , 71 , 68 Given self-determination constructs were not in Elliot's antecedent categories, 3 they were not included. This set of 47 studies resulted in 53 datasets as a few had multiple independent datasets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived competence is an individual's view of his or her present level of ability (Harter, 1982). In the literature on sport, perceived competence has been shown to be positively related to mastery-approach and performance-approach goals in numerous studies (e.g., Cetinkalp, 2012;Morris & Kavussanu, 2009;Zourbanos, Papaioannou, Argyropoulos, & Hatxigeorgiadis, in press); it has evidenced no clear pattern of relations with avoidance-based goals. Translating the 2 Â 2 findings to the 3 Â 2 model, we would expect perceived competence to be positively related to task-approach and/or self-approach goals, as well as other-approach goals, and to be unrelated to avoidancebased goals.…”
Section: Studymentioning
confidence: 99%
“…Achievement goal theory studies have been conducted in the sport environment across the globe in countries such as France [1], Turkey [2], Spain [3], and USA [4]. Achievement goal theory focuses on two main goals that define the purpose of achievement driven behavior.…”
mentioning
confidence: 99%